Three new taxa of Oriental Nanophyini (Coleoptera, Apionidae). - Alonso-Zarazaga, Miguel A. (Contributions to Entomology = Beiträge zur Entomologie, 1990)
Meregallia n. gen. (type species: Nanophyses ligatus Hustache, 1925) and Oxycorax n. subgen. (type species: Shiva dieckmanni n. sp. from Sumatra) are described. Some comments are made on their relationships and on those of the species included in the genus Shiva Pajni & Bhateja, 1982. Nomenclatural ActsMeregallia Alonso-Zarazaga, 1990 (Apionidae), gen. n.dipterocarpi (Marshall, 1932) (Meregallia), comb. n. hitherto Nanophyes dipterocarpiligata (Hustache, 1925) (Meregallia), comb. n. hitherto Nanophyes ligatusOxycorax Alonso-Zarazaga, 1990 (Shiva), sgen. n.dieckmanni Alonso-Zarazaga, 1990 (Shivas (Oxycorax)), spec. n.